A Comparative Analysis of Subjective Quality of the Mobility between a New Portable Electric Transportation Mode and Walking. (16th December 2012) - Ohta, Hiroyuki; Matsumoto, Haruyuki; Fukuda, Daisuke; Fujii, Satoshi
Abstract : To analyze the psychological impacts of the introduction of new portable electric transportation modes, we implemented an experiment using a personal mobile vehicle (PMV). We investigated its effects on 2 types of the subjective quality of mobility (SQM): instrumental aspects including "easiness" and "speed": and affective aspects including "enjoyment, " "seeing scenery, " and "enjoying the atmosphere." The result indicated that PMV might contribute to the improvement of the instrumental aspects of SQM, but walking was regarded as more preferable in terms of the affective aspects. The results suggest that such a new transportation mode could contribute to the improvement of subjective quality of mobility, if and only if it can be introduced in an appropriate situation.